Development of Digital Multimodal Based Public Speaking Learning Media at the Faculty of English Literature University Muslim Al Wahsliyah Medan - Nirmawati, Dita Ainul; Asnawi; Risnawati; Harianto II (PT Inovasi Pratama Internasional, 2025)
Digital media or often also called new media (new digital media) is electronic media stored in digital format (not analog format) which can be used to store, send and receive information digitally. Digital media is internet-based media using sophisticated computers and mobile phones. Digital media as internet-based media has the characteristics of (1) computer-based technology; (2) hybrid characteristics, non-dedicated, flexible; (3) interactive potential; (4) public and private functions; (5) regulations that are not strict; (6) relatedness; (7) ubiquitous/independent of location; (8) can be accessed by individuals as communicators. (4) public and private functions; (5) regulations that are not strict; (6) relatedness; (7) ubiquitous/independent of location; (8) can be accessed by individuals as communicators. (4) public and private functions; (5) regulations that are not strict; (6) linkage; (7) ubiquitous/independent of location; (8) can be accessed by individuals as communicators. This development research will be carried out at the Muslim Nusantara Al Washliyah University in Medan which is located on Jalan Jl. Garu II A No. 93, Harjosari I, Kec. Medan Amplas, Medan City, North Sumatra. This multimodal digital-based public speaking learning media is very effective in improving learning outcomes.